Urologia na graduação médica: como é oferecida e quais fatores influenciam na escolha desta especialidade - Goncalves, Rafael Pauletti (2019)
Introduction: Medical knowledge has increased in the last century. The form of teaching has also evolved, but not all areas of knowledge have adapted, including urology. Given the prevalence of urological diseases and which part of the graduates will act as a general practitioner, good knowledge in the area is required. Objectives: To detail how the knowledge of the field of urology was offered in undergraduate studies and which factors may have influenced the choice of medical residency in urology as a medical specialty. Methodology: This was an observational, cross-sectional, descriptive, quantitative and qualitative study with resident physicians from the urology residency programs of the medical schools of PUC-SP, UFSC and UFRN. The form of contact and factors that contributed to the choice of specialty were obtained through a questionnaire and individual interview. Results: The sample had 15 resident physicians, 40% from schools with traditional curriculum and 60% with active methods. Ninety-three percent reported contact from the 4th year of graduation and 40% of the first activities took place as practical activities. It was found that 33.3% were not trained in bladder catheterization. In the qualitative analysis, 80% reported surgical complexity as a reason for choice and 60% reported that the influence of the teacher motivated the choice. Discussion: Medical education is difficult to evaluate and measure. Published studies show that undergraduate internship in the field of urology has become optional in American schools, but there is much debate about the impact this has on graduates. Conclusion: Our study showed that regardless of the teaching method, exposure in the area of urology occurs in the last years of graduation, with emphasis on the practical part. And the surgical complexity and the influence of the teacher were the factors that influenced the choice of medical residency in urology as a medical specialty